Review on analyzing material in ocular related cosmetics or contact lens products using liquid chromatography-mass spectrometry (LC-MS) and scanning electron microscopy (SEM) / Farah Nasuha Md Zaki - Md Zaki, Farah Nasuha (2016)
INTRODUCTION: Circle contact lenses (CCL) are popular in the markets and there was a pigment that located on front or back surface or enclosed within the matrix of the lens. The purpose of this study was to analyze the material in ocular related cosmetics or contact lens products using LC-MS and SEM. METHODS: The determination the material composed CL products and other ocular related materials was performed using LC-MS and the analyzing of pigment location was performed by SEM to discern the pigment location of the CCL was also analyzed based on the previous studied. RESULTS: The report described the locations of pigment color additives of CCL and also analyzing the CL products and other ocular related from the previous studies. CONCLUSION: The reviews showed the materials or content in ocular related cosmetics or CL product using SEM and LC-MS were important in determining how those products can have effect onto people’s eyes.